The Portrayal of Conversational Narcissism in The Short Film Pemean - Hasna Nurhaliza; Rae Dadela (Universitas Sebelas Maret, 2022)
This qualitative study intends to show how Mbak Sum’s utterances in the short film Pemean flout Grice’s conversational maxim (1975) and lead to the portrayal of conversational narcissism proposed by Vangelisti et al. (1990). Based on the findings, the maxim of quantity is the most frequently flouted maxim in Mbak Sum’s utterances, followed by the maxim of quality and the maxim of relevance. The main conversational implicatures interpreted from the thirteen utterances said by Mbak Sum reveal the act of boasting about Mbak Sum's wealth to provoke admiration and envy from Dek Asih. This study succeeded in revealing a strong connection between the flouting of Gricean maxims and the concept of conversational narcissism in the film. This is proven by the utterances from Mbak Sum that reflect 6 out of 9 important features of conversational narcissistic behaviour as stated in the previous study by Vangelisti and colleagues (1990).